Lateral flow immunoassay for ultrasensitive and affordable naked eye detection of tuberculosis - Ariffin, Nazifah; Yusof, Nor Azah; Abdullah, Jaafar; Ahmad Raston, Nurul Hanun; Kusnin, Norzila (2018)
Lateral flow immunoassays (LFIAs) are advantageous over conventional detection methods in terms of their simplicity and rapidity. These assays have been reported using various types of labels but colloidal gold nanoparticles are still the preferred choice as a label because of their easy synthesis, visual detection and stability. Tuberculosis, or TB, is an infectious bacterial disease caused by Mycobacterium tuberculosis. İt remains one of the deadliest diseases in the world. The detection of Mycobacterium tuberculosis using LFIAs was developed and analyzed using gold nanoparticle.